Corrosion of a chimney liner operated for 130,000 hours - Gwoździk M. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2023)
The tests were carried out for a coal-fired boiler heating a single-family house with a floor area of 220 m2. The tests concerned the chimney lining (structure and surface layer - produced oxides/deposits), hard coal (eco-pea coal) and furnace ash. The chimney liner was located in a chimney made of bricks joined with concrete. A chimney liner made of austenitic steel was tested. The chimney liner was operated for 130,000 hours. The chimney insert was studied on the inside and outside each cross-section. Coal with a grain size of 5–21 mm was analyzed. The bottom ash consisted of both loose ash and a mass of glassy sintered ash, the so-called slag. The thorough examinations of the examined materialsincludec: microscopic examinations with a VHX-7000 digital microscope and Jeol JSM-6610LV scanning electron microscopes. Chemical composition analysis by energy dispersive X-ray spectroscopy (EDS) in conjunction with the scanning electron microscopy (SEM) was performed. The surface topography (roughness) was measured with a VHX microscope using a Gaussian filter. Based on the tests, the following parameters were determined: arithmetic mean height, maximum height, height of the highest peak, depth of the lowest depression, root mean square height, skewness, kurtosis.